A Critical Review on Guduchi (Tinospora cordifolia [willd.] miers) and its Medicinal Properties - Anshu; Singh, Sarvesh Kumar; Rajoria, Kshipra (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: First of all, Tinospora cordifolia, sometimes referred to as “Amrita” or “Guduchi,” is a crucial medication utilized in Indian Systems of Medicine and has been for ages. The Sanskrit term “guduchi” means “which protects the body from diseases.” This herb is also known by the name “Amrita,” which in Hindu mythology alludes to the celestial nectar. Aim: This well-known Indian bitter is recommended for fevers, diabetes, dyspepsia, jaundice, skin conditions, kidney issues, persistent diarrhea, and dysentery. Leprosy, helminthiasis, rheumatoid arthritis, and cardiac problems have all been shown to benefit from it. It is a significant medication that is utilized in a variety of preparations, including Swarasa, Ghrita, Satva, Tail, etc. Material and Methods: For this review article, Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, Ashtanga Sangraha, Bhavprakash Nighantu, Raj Nighantu, Dhanvantari Nighantu, Shaligrama Nighantu, Priya Nighantu, Kaiydev Nighantu, Madanpal Nighantu, Shodhal Nighantu. Results: It has long been recognized that the T. cordifolia plant possesses strong therapeutic, medicinal, healing, and soothing properties. Discussion: Guduchi’s anti-toxic, anti-inflammatory, antipyretic, and anti-oxidant qualities make it a highly promising medicinal herb. In addition, there is no proof that Guduchi contains any harmful substances or adverse effects, demonstrating its safety. Conclusion: T. cordifolia, often known as Giloy, is an herb with medicinal characteristics that can prevent many diseases or abnormalities by naturally boosting immunity in human bodies. These properties are confirmed by the therapeutic and safety aspects research included in this review. Herbal and traditional medicines have a long history and are widely used in India. Natural medicines are becoming more and more important in clinical research these days. In the enormous collection of significant Guduchi (Tinospora cordifolia), one of the medicinal